Pengaruh Penambahan Pupuk Organo Triba Dengan Setengah Dosis NPK Terhadap Pertumbuhan Dan Komponen Hasil Tanaman Kedelai (Glycine Max L. Merril) - Dimas Restu; Husna Yetti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Soybean (Glycine max (L.) Merril) is a type of food that has high nutrition, so it is consumed by many people. The need for soybeans in Indonesia increases every year, while Indonesia's soybean production is not enough to cover soybean needs in Indonesia. This study aims to determine the effect of Organo Triba fertilizer supplemented with half the dose of NPK and get the best dosage for growth and components of soybean yields and compare with full dose NPK recommendations. This research was carried out in the experimental garden of the Faculty of Agriculture, University of Riau. This study used a randomized block design (RBD) of 1 factor and 4 replications with a control level as a comparison. The factors used were 5 doses of tribal organo fertilizer with 1/2 dose of NPK fertilizer and control levels with recommended dosage NPK without tribal organo. The results showed that 1.5 ton.ha-1 tribal fertilizer with 1/2 dose of NPK showed better results among other treatments in increasing the number of branches. Organo Triba fertilizer with 1/2 dose of NPK does not increase the yield component, because the nutrients that are sufficient in the growing media. Keywords: Soybean, Organo Triba fertilizer, NPK fertilizer